Complex permittivity, permeability and microwave absorbing properties of PANI coated MWCNTs/ Manganese Zinc ferrite nanocomposite. (2019) - Tammareddy, Haritha; Ramji, K.; Naga Sree, P. Siva; Santhosi, B.V.S.R.N.
Abstract: The complex permittivity, complex permeability and microwave absorbing properties of nanocomposites containing dielectric/magnetic fillers have been investigated in X-band (8.2-12.4 GHz) frequency range. Nano composites have been fabricated using polyaniline coated MWCNTs and Manganese Zinc Ferrite nano powder fillers into epoxy matrix. The Polyaniline coated MWCNT were prepared by in-situ polymerization. Manganese Zinc ferrite nano powder was synthesized by sol-gel auto combustion process. Dielectric, Magnetic and Hybrid nano composites of different weight percentages were fabricated and tested for permittivity, permeability and microwave absorption properties in X-band frequency using a vector network analyzer. Dielectric measurements revealed that the real and imaginary parts of permittivity and permeability increased with increase in the concentration of the filler. MATLAB code developed based on fundamentals of EMW theory using impedance matching condition was used to measure microwave absorption. Simulation studies have been carried out for four layered composites with epoxy as first layer and their reflection losses were determined.